Learning Maximum Absolute Meaning Through Reasoning About Speaker Intentions. Issue 2 (4th November 2020) - Lee, Crystal; Kurumada, Chigusa
Abstract: Three experiments investigated adult learners' acquisition of a novel adjective. In English and other languages, meanings of some gradable adjectives are said to include an absolute standard of comparison (e.g., full means completely filled with content). However, actual usage is often imprecise, where a maximum absolute standard of comparison, strictly speaking, does not apply (e.g., a 90% full cup can be full depending on how it will be used). This creates problems for learners who acquire the absolute meaning from variable mappings between word forms and observations. We demonstrated that adult learners infer a maximum standard of comparison when they receive information about agents' intended goals that lie behind imprecise word usage. Results suggested these inferences are conditioned on the amount of visually ambiguous observations made during learning. We conclude that access to agents' intended goals allows learners to explain contextual sources of imprecision and helps the learning of a maximum absolute meaning from primarily nonabsolute observations. Abstract :